1987
DOI: 10.1016/0014-5793(87)81255-3
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody to fibronectin which inhibits extracellular matrix assembly

Abstract: A monoclonal antibody L8 specific to fibronectin was shown to inhibit fibronectin incorporation into the fibroblast extracellular matrix. Antibody L8 could not interact with fibronectin complexed with gelatin. The results suggest the existence of a specific site on the fibronectin molecule playing a critical role in the assembly of the fibronectin extracellular matrix. This site is located near the collagen-binding domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…One possible explanation is that domain III-1 is opened in fibrils, but the cysteine becomes buried in an FN-FN bond. Previous work has implicated III-1 in FN fibril assembly (27)(28)(29). Conversely, domains III-6 and III-12 showed no labeling in solution but showed significant labeling in stretched fibrils, suggesting that these domains are unfolded specifically in matrix fibrils.…”
Section: Table 2 Relative Rates Of Fn-iii Domain Openingmentioning
confidence: 83%
“…One possible explanation is that domain III-1 is opened in fibrils, but the cysteine becomes buried in an FN-FN bond. Previous work has implicated III-1 in FN fibril assembly (27)(28)(29). Conversely, domains III-6 and III-12 showed no labeling in solution but showed significant labeling in stretched fibrils, suggesting that these domains are unfolded specifically in matrix fibrils.…”
Section: Table 2 Relative Rates Of Fn-iii Domain Openingmentioning
confidence: 83%
“…The first FNIII domain consists of a beta sandwich that may be stretched into an open conformation by local cell traction forces. A cryptic site is revealed in this open configuration that is important for intermolecular fibronectin binding, and this site contains a specific epitope for the L8 monoclonal antibody (Chernousov et al, 1987;Hocking et al, 1994;Smith et al, 2007;Zhong et al, 1998). The L8 antibody labeled Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Remodeling of the fibronectin matrix in response to III1c occurs rapidly, does not require the presence of cells and is not accompanied by changes in the levels of fibronectin matrix. Previous studies have indicated that the III1 region of fibronectin participates in homophilic binding interactions among fibronectin molecules, which can regulate the assembly of the fibronectin matrix (Chernousov et al, 1987;Chernousov et al, 1991;Hocking et al, 1994;Hocking et al, 1996;Morla et al, 1994;Morla and Ruoslahti, 1992). Reports on the effects of the III1c peptide on the IST-9 Fig.…”
Section: Discussionmentioning
confidence: 99%